Charcot–Marie–Tooth disease: frequency of genetic subtypes and guidelines for genetic testing. Issue 7 (10th May 2012) - Murphy, Sinead M; Laura, Matilde; Fawcett, Katherine; Pandraud, Amelie; Liu, Yo-Tsen; Davidson, Gabrielle L; Rossor, Alexander M; Polke, James M; Castleman, Victoria; Manji, Hadi; Lunn, Michael P T; Bull, Karen; et al.
Abstract : Background: Charcot–Marie–Tooth disease (CMT) is a clinically and genetically heterogeneous group of diseases with approximately 45 different causative genes described. The aims of this study were to determine the frequency of different genes in a large cohort of patients with CMT and devise guidelines for genetic testing in practice. Methods: The genes known to cause CMT were sequenced in 1607 patients with CMT (425 patients attending an inherited neuropathy clinic and 1182 patients whose DNA was sent to the authors for genetic testing) to determine the proportion of different subtypes in a UK population. Results: A molecular diagnosis was achieved in 62.6% of patients with CMT attending the inherited neuropathy clinic; in 80.4% of patients with CMT1 (demyelinating CMT) and in 25.2% of those with CMT2 (axonal CMT). Mutations or rearrangements in PMP22, GJB1, MPZ and MFN2 accounted for over 90% of the molecular diagnoses while mutations in all other genes tested were rare. Conclusion: Four commonly available genes account for over 90% of all CMT molecular diagnoses; a diagnostic algorithm is proposed based on these results for use in clinical practice. Any patient with CMT without a mutation in these four genes or with an unusual phenotype should be considered for referral for an expert opinion to maximise the chance of reaching a molecular diagnosis.